Factors Determinating Employee Confidence in the Management System Anti-Bribery at PLN UPT Kendari - Nelvia, Helda; Hasbullah, Hasbullah; Amiruddin, Amiruddin; Syamsuddin, Syamsuddin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to evaluate the effectiveness of the ISO 37001:2016 Anti-Bribery Management System (SMAP) at PLN UPT Kendari, especially in increasing employee confidence in the anti-bribery system. The research method used is a quantitative approach with multiple linear regression analysis to test the influence of policy understanding variables, clarity of reporting procedures, and the effectiveness of socialisation on employee confidence. The results showed that understanding policies and clarity of reporting procedures significantly and positively influenced confidence in SMAP. In contrast, the effectiveness of socialisation did not have a significant influence. An R-squared value of 68.2% indicates that this model can explain most of the variability of confidence in anti-bribery systems. The classical assumption test also supports the validity of this regression model. Based on the study results, it is recommended that PLN UPT Kendari increase the intensity of socialisation through a more interactive approach, strengthen continuous training, and simplify bribery reporting procedures. These steps are expected to improve the implementation of SMAP at PLN UPT Kendari and create a work environment with high integrity.